2015
DOI: 10.1007/s00586-015-4290-6
|View full text |Cite
|
Sign up to set email alerts
|

A validated preoperative score predicting survival and functional outcome in lung cancer patients operated with posterior decompression and stabilization for metastatic spinal cord compression

Abstract: Purpose This study aims to create and validate a score for survival and functional outcome of lung cancer patients with metastatic spinal cord compression (MSCC) after posterior decompressive surgery. Methods The entire cohort of 73 consecutive patients was randomly assigned to a test group (N = 37) and a validation group (N = 36). In the test group, we retrospectively analyzed 10 preoperative characteristics. Characteristics significantly associated with survival on multivariate analysis were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…2,3,5,7,15,18,19,21,25,28,[30][31][32]34,35,37,38,40,43 Of these, 16 studies were retrospective; 1 was a longitudinal observational study; 1 was a randomized, multiinstitutional, nonblinded trial; and 1 was a semiprospective study that included both retrospectively and prospectively collected data. Surgical interventions included decompression with and without instrumentation and radiotherapy.…”
Section: Predictors Of Survivalmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,5,7,15,18,19,21,25,28,[30][31][32]34,35,37,38,40,43 Of these, 16 studies were retrospective; 1 was a longitudinal observational study; 1 was a randomized, multiinstitutional, nonblinded trial; and 1 was a semiprospective study that included both retrospectively and prospectively collected data. Surgical interventions included decompression with and without instrumentation and radiotherapy.…”
Section: Predictors Of Survivalmentioning
confidence: 99%
“…7 Additionally, the authors noted that KPS was the strongest predictor of survival in the their hormonerefractory patients. 7 Lei et al 21 sought to establish a scoring system for survival and functional outcome among patients undergoing posterior decompression surgery for lung cancer metastatic to the spine. The authors found that preoperative ambulatory status (p < 0.01), visceral metastases (p < 0.001), and time to developing motor deficits (p < 0.001) were significant predictors of survival and were therefore included in the scoring system.…”
Section: Predictors Of Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Predicting functional outcome is of great importance when selecting the appropriate treatment in MESCC patients [14][15][16].…”
Section: Discussionmentioning
confidence: 99%